DEVELOPMENT OF ARBUSCULAR MYCHORRHIZHAE AND GROWTH OF TEAK (Tectona grandis Linn. F.) SEEDLINGS INOCULATED WITH SPORES OF ARBUSCULAR MYCORRHIZAL FUNGI ORIGINATED FROM SOIL IN TEAK FOREST - Corryanti Corryanti; Joedoro Soedarsono; Bostang Radjagukguk; Siti Muslimah Widyastuti (Jurnal Pemuliaan Tanaman Hutan, 2007)
The objective of the study was to determine the effect of arbuscular mycorrhizal fungi collected from soil of teak plantation forest on the growth of teak seedling related to mycorrhizal association development. The study utilized the complete randomized design with three levels of inoculant’s factor, consisting of control (uninoculated), inoculation with Gigaspara spores and inoculation with Glomus spores inoctilated, with ten replications. Spores isolated originated from soil of teakplantation forest in Tangen, Surakarta. The planting medium was a mixture soil sand at 1:1 (v/v) sterilized prior to be used. NPK mixed ferfilizer was applied at amount 0,0625 gr per seeadling mixed in to the planting medium. Measurements were conducted during a five month period. The data were analyzed using the Analysis ofVariance method and differences among treaments analyzed usfing the Duncan’sMultiple Range Test at the 5% ievel of significance. The results showed that inoculationwith the arbuscular mycorrhizail fungi increased teak seedling growth, with Gigaspora sp inoculation giving the highest growth. The uptakes of N, P, K and Ca were increased by both Gigaspora sp and Glomus sp inoculations. The increased seedling growth, was accompanied by large increases in infection percentage as well as sporulation. The highest infection and sporulation  were found with Gigaspora sp inoculation. These results showed that in the soil ofteak plantation forest in Tangen of the grumusol type, relatively low NPK fertilization (0,0625 gr per seedling) and inoculadon with spores ofarbuscular mycorrhizal fungi improved teak seedling growth, inereased nutrient uptake, as well as improved mycorrhizal association development in teak seedlings.